ATTRIBUTES OF IMPROVING SERVICE QUALITY ON CONSUMER SATISFACTION WITH SERVQUAL APPROACH - Poniman Poniman; Yitno Utomo (UNIPA PRESS, 2020)
This research aim to find out service quality attributes that can increase customer satisfaction. One service company is CV. Nirwana which is engaged in the sale and service of office equipment maintenance. winning business competition company must create a strategy that can improve the quality of service to consumers.Themethod used in this study is the ServQual Method which includes 5 main dimensions, namely Tangibles, Reliability, Responsiveness, Assurance and Emphaty. The ServQual method is a tool used to measure the services or products of the quality of services received by consumers. Based on the level of service quality there is a negative attribute value on the variable on the dimensions of reliability and responsiveness. Negative values indicate that the quality of service is not quality and consumers do not feel satisfaction with the services provided by the company. Positive values are found in the tangibles, assurance and empathy variables which show that the service provided can be said to be a surprise and consumers feel satisfaction with the service. Therefore, the company is expected to be able to improve the quality of services that are of negative value, namely engine cleanliness after repairs, speed and timeliness in providing services, seriousness and reliability of technicians in completing repairs, availability of historical data / recording systems that are good at service, providing service services in accordance with promise, Alertness in providing assistance to consumers if experiencing difficulties Provide a good explanation of repairs, costs and estimated time to consumers, the ability of service advisors in diagnosing customer problems / complaints.